"И доброту во всем ищу...": люди и время : [сборник / составитель В. В. Корепанов] - Корепанов В. В. (2015)
Экземпляры: ЦБ (20200316) / Инвентарный номер: 51917 / Цена: 120.00 / Сис.шифр: 84(2Рос=Удм) / Авт.знак: И 11 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Удм)6